A Comparative Study on the Memory-Enhancing Actions of Oral Renin-Angiotensin System Altering Drugs in Scopolamine-Treated Mice. Issue 5 (August 2019) - Ababei, Daniela Carmen; Bild, Veronica; Ciobică, Alin; Lefter, Radu Marian; Rusu, Răzvan Nicolae; Bild, Walther
This study was designed to evaluate the spatial working memory (as studied in Y-maze) or short-term and long-term spatial memory (assessed in radial 8 arms-maze task), in a scopolamine-induced memory deficits model in mice, by the oral administration of 2 angiotensin-converting enzyme inhibitors—captopril and ramipril and also the effects of the AT1 receptor antagonist, losartan. The present article was initiated as a reaction to the clinical setting of hypertensive disease, which involves lifelong administration of antihypertensive drugs, dietary or lifestyle constraints, and aging, which all take a toll on the higher functions of the nervous system. Most of the patients with cognitive decline suffer of various metabolic imbalances, hypertension, cardiac and kidney disease, many of them which are treated with oral administration of Renin–angiotensin aldosterone system-altering agents like those presented above. Our results showed a protective effect of captopril, ramipril, and losartan prescopolamine administration on spontaneous alternation in Y-maze task, as compared to scopolamine-alone treated mice, as well as decreased number of working memory errors and reference memory errors in radial-arm maze for both losartan + scopolamine and ramipril + scopolamine groups versus scopolamine alone. This could have a therapeutical relevance, especially since oral administration was preferred in our report, as it is used in the therapeutic procedures in humans, further enhancing the similarities with the clinical conditions.